Post-Cholecystectomy Biliary Dilatation - Muhammad Alam, Siddique Ahmad, Ali Gohar Khan, Sheema Amin, Rizmi Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Despite the fact that the common bile duct (CBD) is thought to dilate following surgery, post-cholecystectomy CBD dilatation still remains a source of debate. Intravenous cholangiography made it possible to measure the common duct directly. Although most patients did not have a substantial increase in duct diameter following cholecystectomy, there was a trend toward a modest degree of duct dilatation, according to prospective studies employing sonography to assess the common duct. Objective: To determine the frequency of common bile duct dilatation after cholecystectomy for chronic cholecystitis. Study Design: Descriptive study Place and Duration of Study: General Surgery Department, Hayatabad Medical Complex, Peshawar from 1st February 2020 to 31st January 2021. Methodology: Eighty seven patients and age range is 20-60 years booked for cholecystectomy in outpatient department were included and followed up to 6 month to determine the frequency of common bile duct dilatation. Results: The mean age was 38.6±10.3 years with 25 (28.7%) males and 62 (71.2%) females. Mean body mass index of the sample was 25±2.3kg/m2. Sixty (68.9%) underwent laparoscopic cholecystectomy while 17 (19.5%) underwent open cholecystectomy. Mean baseline common bile duct diameter on ultrasound was 1.3±0.1 mm while the mean follow up common bile duct diameter was 1.8±0.2 mm (p<0.001). Common bile duct dilatation was recorded in 20 (22.98%) patients. Conclusion: Common bile duct dilatation after cholecystectomy is controversial, but in asymptomatic patients, a dilation of up to 10mm should be accepted as normal. Keywords: Cholecystectomy, Cholecystitis, Common bile duct dilatation, Body mass index